The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1149/2162-8777/abbb9f
|View full text |Cite
|
Sign up to set email alerts
|

Novel Research on CuONPs/MWCNTs Effect on the Properties of Na-Bentonite Water Based Drilling Muds with Experimental Study

Abstract: This novel research, aimed to improve the properties of Na-bentonite water based drilling mud (WBDM) and reduce its cost by adding multi-walled carbon nanotubes functionalized with copper oxide nanoparticles (CuONPs/MWCNTs). For this purpose, fistly, copper oxide nanoparticles (CuONPs) and multi-walled carbon nanotubes (MWCNTs) were synthesized separately, then MWCNTs were functionalized with CuONPs by chemical vapor deposition (CVD) method. Secondly, CuONPs/MWCNTs were characterized by X-ray Photoelectron Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The resulting precipitate was then washed 3 times with distilled water. Finally, CuONPs were obtained by drying the precipitate at 100 °C for about 24 h. 36,37 Synthesis of multi-wall carbon nanotubes functionalized with copper oxide (CuONPs/MWCNTs) nanocomposite.-CuONPs/ MWCNTs nanocomposite was synthesized by the CVD method. As a carbon source in this synthesis; a dispersion containing multi-walled carbon nanotubes + nanoparticle material (1:1 v/v) was used.…”
Section: Production Of Multi-walled Carbon Nanotubes (Mwcnts)-mentioning
confidence: 99%
“…The resulting precipitate was then washed 3 times with distilled water. Finally, CuONPs were obtained by drying the precipitate at 100 °C for about 24 h. 36,37 Synthesis of multi-wall carbon nanotubes functionalized with copper oxide (CuONPs/MWCNTs) nanocomposite.-CuONPs/ MWCNTs nanocomposite was synthesized by the CVD method. As a carbon source in this synthesis; a dispersion containing multi-walled carbon nanotubes + nanoparticle material (1:1 v/v) was used.…”
Section: Production Of Multi-walled Carbon Nanotubes (Mwcnts)-mentioning
confidence: 99%
“…Drilling fluid is indispensable the drilling process, called the blood of drilling [ 12 , 13 ]. It flows in from the drill pipe and out in the gap between the drill pipe and the formation, and it has various effects such as carrying rock chips, protecting the well bore, balancing the formation pressure, assisting in breaking rock, etc.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the PV value increased 57%, the AV value 36.7%, the YP value 28%, the 10 s and 10 min values increased 33.3% and 44.4%, respectively, and the fluid loss value decreased by 13.8%. 16 As a result of their work by adding 0.001%-0.01% SiO 2 NPs/MWCNTs to water-based drilling mud; they found that PV, AV, YP, 10 s and 10 min, cake thickness values increased by 71.4%, 51.9%, 44%, 25%, 33.3% and 11%, respectively. They also reported that the amount of filtration loss decreased by 13.8%.…”
mentioning
confidence: 98%
“…They also reported that the amount of filtration loss decreased by 13.8%. 17 Özkan added AuNPs/MWCNTs to the water-based drilling muds in his work in 2020. In the results of working; the PV value of the water-based drilling mud increased by 85.7%, the AV value was 113%, the YP value was 187.5%, the gel strength values (10 s and 10 min) increased by 275% and 166.6%.…”
mentioning
confidence: 99%